Adrenal disease: The GP's role. Issue 2 (February 2015) - Mears, Ruth; Roberts, Aled
The adrenal glands sit above the kidneys and consist of an outer adrenal cortex and an inner adrenal medulla. The adrenal cortex is responsible for the production of aldosterone (a mineralocorticoid), cortisol (a glucocorticoid) and sex steroid precursors (pre-androgens). The adrenal medulla is functionally part of the sympathetic nervous system and contains chromaffin cells that release noradrenaline and adrenaline (catecholamines). Disorders of the adrenal gland may result in over- production of hormones, for example, excess glucocorticoids causing Cushing's syndrome, excess mineralocorticoids causing primary hyperaldosteronism or excess catecholamines (phaeochromocytoma), or under-production such as in Addison's disease (also known as primary adrenal failure), which is a deficiency of glucocorticoids and mineralocorticoids. This article explores these four conditions in greater depth to help GPs have a greater understanding of their role in the diagnosis and management of adrenal disorders.